Sigur Rós's Heima: An Icelandic Psychogeography - Mitchell, Tony (Transforming Cultures eJournal, 2009)
This paper examines the sonic geography of the Icelandic ambient rock group Sigur Rós with particular reference to their documentary film Heima, which documents a tour the group made of remote places in their home country. Known for causing some people to faint or burst into tears during their concerts, Sigur Rós’s music could be said to express sonically both the isolation of their Icelandic location and to induce a feeling of hermetic isolation in the listener through the climactic and melodic intensity of their sound. This is distinguished by lead guitarist Jónsi Birgisson’s falsetto vocals and Gibson Les Paul guitar played through reverb with a well-resined cello bow, heavily amplified drums, and the use of various types of keyboards, including church organ, minimally emphatic bass, and an all-female string section called Anima who play instruments such as xylophone, celeste, a glass of water, a musical saw and a laptop. Singing both in Icelandic and an invented language called Hopelandic (vonlenska), Jónsi, who is gay and blind in one eye, channels a striking form of glossolalia in his vocals which links the group’s music to ambient rock predecessors such as the Cocteau Twins and Dead Can Dance. As Edward D. Miller has stated, ‘Glossolalia reveals the tension between voice and signification, and exposes the communicativeness of sounds itself. The casual listener to Sigur Rós easily becomes an involved one. S/he is listening to made up words and in accepting the meaning of their arrangement in a melody, imagines what the lyrics might mean. This dual dynamic creates a strong emotional correspondence between the band and its listener’ (2003: 8). The group acknowledges a strong degree of Icelandic animism in their music – they have referred to ‘the presence of mortality’ in the Icelandic landscape, and their links to stories, sagas, magic and ritual in a remote country where ‘the majority of the population believes in elves and power spots … the invisible world is always with us’ (Young 2001:33). In their music they create geomorphic soundscapes which transport the active listener into an imaginary world. As bass player Georg Holm, who is demophobic, has stated, ‘we provide the colours and the frame and you paint the picture’ (Zuel 2005). This paper mobilises Barthes’ ‘jouissance’, Michael Bull’s work on personal stereos, and Daniel Grimley’s work on music and Nordic identity along with various notions of musical affect to discuss relations between Sigur Rós’s music, arctic landscape and its resonances outside Scandinavia.